Emergence of Enhanced Quality Expectations in Pharmaceuticals - Obaid , Roohi Bano; Ali, Obaid (International Journal of Endorsing Health Science Research, 2018)
Commercial viability of any drug product may often bring pain for patients who otherwise wait for their drug to improve their quality of life and breath. Dryness of drug products like thyroxin, warfarin, phenobarbitone, salbutamol inhalers, morphine etc. from the market leave patient on the mercy of nature. The heart wrenching healthcare professional burst out when lifesaving drugs are not available due to any reason. Voice of civil society rises in community where care of others is felt as a moral responsibility beside capitalism and/or socialism. It is also observed and quite possible that quality defects may create similar situations of drug shortage. Manufacturing facility or its control may go out unwittingly due to knowledge limitation. A quality defect that impacts delivery and performance of drug and/or carries harmful potential has always been a matter of top priority. In both cases, ability to detect, report and assess defines presence and thickness of protection wall for the public. Power to predict uncertainty and taking measures well in time is a challenge for industry and regulators to maintain uninterrupted supply of quality drugs.